2012
DOI: 10.1002/jez.b.22447
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Hair Evolution Based on Some Comparative Studies on Vertebrate Cornification

Abstract: Hair evolution contributed to the biological success of mammals. Hair origin from synapsid scales is speculative and requires extensive modifications of the morphogenetic process transforming lens-shaped dermis of scales into small dermal papillae in hair. Hair evolution from glands is hypothetical but is supported from studies on the signaling control of hair vs. glandular morphogenesis. Based on immunocytochemical and comparative studies, it is hypothesized that the onion-like organization of hair derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Thus, the nonkeratin genic component of feather development arose deep in vertebrates and the greatest signal of regulatory innovation was coincident with the burst of phenotypic change associated with the transition to land. Although information on the integument of the ancestral amniote remains exceptionally limited ( Alibardi et al 2009 ; Alibardi 2012 ), the accumulation of CNEEs inferred to have occurred at this time indicates a key role for regulatory change during this transition and in the subsequent evolution of vertebrate integumentary diversity. Consistent with this hypothesis, 32 genes in our feather gene set are here identified as shared with those involved in the development of mammalian hair ( Lowe et al 2011 ) (hypergeometric distribution, P < 1e-80; supplementary table S3 , Supplementary Material online) and present in the amniote ancestor.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, the nonkeratin genic component of feather development arose deep in vertebrates and the greatest signal of regulatory innovation was coincident with the burst of phenotypic change associated with the transition to land. Although information on the integument of the ancestral amniote remains exceptionally limited ( Alibardi et al 2009 ; Alibardi 2012 ), the accumulation of CNEEs inferred to have occurred at this time indicates a key role for regulatory change during this transition and in the subsequent evolution of vertebrate integumentary diversity. Consistent with this hypothesis, 32 genes in our feather gene set are here identified as shared with those involved in the development of mammalian hair ( Lowe et al 2011 ) (hypergeometric distribution, P < 1e-80; supplementary table S3 , Supplementary Material online) and present in the amniote ancestor.…”
Section: Resultsmentioning
confidence: 96%
“…. Therefore this new hypothesis would sustain the scaling origin of hairs from a scaled reptilian integument (Spearman, ; Maderson, ; Alibardi, ), an alternative to the glandular hypothesis of hair evolution (Stenn et al, ; Dhouailly, ; Alibardi, ).…”
Section: Discussionmentioning
confidence: 98%
“…The paucity of Lagerstätten preserving hairs (15/143, 10%) is surprising given the proposed high potential for hair preservation [72] and significant mammalian biodiversity in the Cenozoic (figure 3c). Differences in the preservation potential of a-keratin due to the differences in its chemical structure relative to that of feather keratin [26] and/or the ability to identify isolated hairs may explain this pattern. Recent fossil evidence has suggested that hairs may pre-date the phylogenetic divergence between monotremes and other crown mammals (eutherians and metatherians) [60].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we asked what factors might explain these patterns of uneven preservation potential of integuments through time. Given variation in the chemistry of their components [26], variation in resistance to decomposition in distinct integumentary structures may be expected [72,77]. Among integument types, only the limited record of hair preservation in 15 total Lagerstätten was significantly predicted by biodiversity (figure 2b; electronic supplementary material, figure S11).…”
Section: Discussionmentioning
confidence: 99%